Large amplitude oscillatory shear (LAOS) measurements as a promising tool to predict electrospinnability of pectin solutions - Ozmen, Duygu; Balik, Busra Akinalan; Argin, Sanem; Yildirim-Mavis, Cigdem; Toker, Omer Said (WILEY, 2022)
The response of the polymer solution to % strain is critical since the polymer solution is drawn by the electrical field during electrospinning process. To date, all studies relating electrospinning to rheological parameters have been conducted in the linear region where small strain values are applied to the polymer solutions. This is the first study attempting to correlate the behavior of the solutions in the nonlinear region with smooth nanofiber formation. For this aim, fiber forming solutions were prepared with pectin at different concentrations (3%, 4%, 5%, and 6%) and PEO with different molecular weights (600, 1000, and 2000 kDa). Deformation was applied in the range of 0.05% and 500% and normalized Lissajous curves were obtained. Both elastic and viscous curves confirmed one another, suggesting a profound contribution of PEO (2000) to the elasticity of the polymer solution at all pectin concentrations even at large strain values. This finding might explain why smooth fibers can only be achieved with PEO (2000) while only beaded fibers were formed with PEO (600) and PEO (1000). The results suggest that LAOS measurements might be used as a promising tool to predict whether a polymer solution can be electrospun into smooth nanofibers.
Keywords: biomaterials; electrospinning; LAOS; nanofiber; rheology; viscosity and viscoelasticity; CARRIER POLYMER; BEHAVIOR; NANOFIBERS; OXIDE; VISCOELASTICITY; Polymer Science